Energy Level Engineering in Organic Thin Films by Tailored Halogenation. (22nd June 2020) - Ortstein, Katrin; Hutsch, Sebastian; Hinderhofer, Alexander; Vahland, Jörn; Schwarze, Martin; Schellhammer, Sebastian; Hodas, Martin; Geiger, Thomas; Kleemann, Hans; Bettinger, Holger F.; Schreiber, Frank; Ortmann, Frank; et al.
Abstract: In modern electronics, it is essential to adapt band structures by adjusting energy levels and band gaps. At first sight, this "band structure engineering" seems impossible in organic semiconductors, which usually exhibit localized electronic states instead of Bloch bands. However, the strong Coulomb interaction in organic semiconductors allows for a continuous shift of the ionization energy (IE) over a wide range by mixing molecules with halogenated derivatives that exhibit different quadrupole moments. Here, this effect of energy level engineering on blends of pentacene and two fluorinated derivatives, in which the position but not the number of fluorine atoms differ, is studied. Structural investigations confirm that pentacene forms intermixed phases in blends with the fluorinated species. The investigation of electronic properties and simulations reveals a much larger shift of the ionization energy (1.5 eV) than in previous studies, allowing to test this model in a range not investigated so far, and emphasizing the role of the position of the halogen atoms. The tuning effect is preserved in electronic devices such as field‐effect transistors and significantly influences device characteristics. Abstract : The effect of energy level engineering is investigated on blends of pentacene and two fluorinated derivatives. The investigation of structure and electronic properties reveals a new record in the shift of the ionization energy and emphasizes the role of the position of the halogen atoms. Characterizations of organic field‐effect transistors show the influence on devices.